Detection of viral antigens associated with cervical cancer agents and precursors - Jara, Delia (2015)
OBJECTIVE: To determine the prevalence of viral antigens (HPV, CMV and HSV2) in cervical cancer and precursors. DESIGN: Expression of viral antigens is studied by inmune bistochemistry (LSAB) in 91 cervical biopsies with diagnosis of squamous intraepithelial lesion (low and high grade IEL) and invasive squamous carcinoma in 94 patients with history of abnormal citology. RESULTS: Viral antigens expressed in 81 of 91 cases (89%), either alone (46%) or combined (42%). In 58% HPV was detected (57% in low grade IEL, 60% bigb grade IEL and 50% invasive cancer), and in 45% CMV (57% low grade IEL, 35% high grade IEL and 17% squamous carcinoma). Significant differences were noted in the 3 viral antigens expression in high grade lesions (p > 0, 05). CONCLUSIÓN: Prevalence of viral antigens in this group is related to cervical tumor; HPV was the viral antigen most frequently detected in cervical cancer and preclínical lesions.